1997
DOI: 10.1016/s0009-2509(96)00398-3
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 1,1′-bi-2-naphthol enantiomers by continuous chromatography in simulated moving bed

Abstract: Abstract--The chromatographic separation of 1,1'-bi-2-naphthol enantiomers with 3,5-dinitrobenzoyl phenylglycine bonded to silica gel stationary phases is studied. Continuous chromatography in simulated moving bed (SMB) is analyzed by modeling, simulation and operation of a SMB pilot unit Licosep 12-26 from Separex (France).A model for the prediction of the cyclic steady-state performance of the SMB is developed based on the analogy with the true moving bed (TMB). The model assumes axial dispersion flow for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 33 publications
2
51
0
1
Order By: Relevance
“…The purified bi-naphthol enantiomers are used as chiral building blocks in asymmetric synthesis and as catalysts in some chemical reactions. The enantioseparation can be carried out using 3,5-dinitrobenzoyl phenylglycine bonded to silica gel as stationary phase and heptane-isopropanol (72:28) as eluent [11,12]. A bi-Langmuir model is proposed to describe the adsorption equilibrium isotherms, which were measured by the Novasep group [13]: Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified bi-naphthol enantiomers are used as chiral building blocks in asymmetric synthesis and as catalysts in some chemical reactions. The enantioseparation can be carried out using 3,5-dinitrobenzoyl phenylglycine bonded to silica gel as stationary phase and heptane-isopropanol (72:28) as eluent [11,12]. A bi-Langmuir model is proposed to describe the adsorption equilibrium isotherms, which were measured by the Novasep group [13]: Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The eluent used was a 72/28 (v/v) heptane-isopropanol mixture. Operation temperature was fixed at 25°C [11,12].…”
Section: Experimental Operation Of a Smb Pilot Unitmentioning
confidence: 99%
“…SMB 기술은 1960년대 초기 UOP 사 에서 개발하였고, 그 이후로 다양한 분야에 적용되기 시작했다 [1,2]. 대표적으로 정밀화학산업 [3,4], 제약 분야의 고순도 정제 [5], 아미노 산과 단백질 정제 [6,7], 제당 산업의 HFCS (high fructose corn syrup) …”
Section: 서 론unclassified
“…A more complete study of the influence of other model parameters can be found elsewhere [16,25]. 7.20) where i = A, B represents the component (A is the less retained, B the more retained component).…”
Section: Simulation Of Smb Processesmentioning
confidence: 99%